A systematic literature review of illicit financial flows and money laundering: Current state of research and estimation methods - Popik-Mazur Anna (Journal of Economics and Management, 2025)
Aim/purpose – The goal of the paper is to examine the current state of research on illicit financial flows (IFF) and money laundering (ML) with a specific focus on detection and estimation methods. This study seeks to identify and evaluate the most promising approaches that can effectively counter IFF and ML in the context of economic stability, ensuring they remain adaptive to constantly evolving threats.